A physical perspective to understand myelin II: The physical origin of myelin development - Liu, Yonghong; Yue, Wenji; Yu, Shoujun; Zhou, Tian; Zhang, Yapeng; Zhu, Ran; Song, Bing; Guo, Tianruo; Liu, Fenglin; Huang, Yubin; Wu, Tianzhun; Wang, Hao (Frontiers in Neuroscience, 2022)
The physical principle of myelin development is obtained from our previous study by explaining Peter's quadrant mystery: an external applied negative and positive E-field can promote and inhibit the growth of the inner tongue of the myelin sheath, respectively. In this study, this principle is considered as a fundamental hypothesis, named Hypothesis-E, to explain more phenomena about myelin development systematically. Specifically, the g-ratio and the fate of the Schwann cell's differentiation are explained in terms of E-field. Moreover, an experiment is proposed to validate this theory.